Passage of The Health Law: A Human Rights Perspective in The Field of Public Services - Widjaja, Gunawan (Lafadz Jaya Publisher, 2025)
The passing of the Health Law is a strategic step in strengthening human rights guarantees in the field of public services, especially access to health services. This law affirms the state's commitment to fulfil the basic right of the people to quality health in an equitable manner. However, the main challenge lies in reducing regional disparities and ensuring that vulnerable groups are not left behind in obtaining services that are inclusive and based on social justice. Through a human rights approach, Health Law has great potential to realise a more equitable and comprehensive national health system. With proper monitoring and implementation, this law can be the main foundation for achieving rights-based and equitable public services.